Peningkatan Hasil Belajar IPS Siswa SMP Melalui Model Pembelajaran Discovery Learning - Yulianta, Agus Giri; Syahril, Syahril (SCAD Independent, 2025)
The purpose of this study was to improve the learning achievement of social studies students on international trade material by implementing the discovery learning model in class IX.4 of SMP Negeri 16 Batam during the 2018/2019 academic year. This research was carried out through classroom action research which consisted of two cycles, where each cycle included stages of planning, implementation, observation, and reflection. The discovery learning model was chosen because it encourages students to play an active role in the learning process, especially in exploring concepts, identifying problems, and finding solutions independently or collaboratively. Data collection techniques in this study included documentation to obtain information regarding student learning outcomes and observation sheets to monitor learning activities and the extent of student involvement during the implementation of discovery learning. The collected data were analysed descriptively qualitatively to describe the improvement in student achievement from one cycle to the next. The results of the study show that the application of discovery learning has a positive impact on students’ understanding of international trade material. This is evident from the increase in the percentage of students who achieved mastery learning, where in cycle I the completeness level reached 68%, and after improvements and refinements to the learning process, student mastery increased significantly in cycle II to 85%. These findings indicate that discovery learning is effective in improving social studies learning outcomes and can be used as an alternative model in developing students’ analytical and conceptual skills, particularly in economic-related materials such as international trade.